2023
DOI: 10.3390/genes14040863
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Assembly and Comparative Analysis of Actinidia latifolia and A. valvata Mitogenomes

Abstract: Kiwifruit (Actinidia) has been recently domesticated as a horticultural crop with remarkably economic and nutritional value. In this study, by combining sequence datasets from Oxford Nanopore long-reads and Illumina short-reads, we de novo assembled two mitogenomes of Actinidia latifolia and A. valvata, respectively. The results indicated that the A. latifolia mitogenome has a single, circular, 825,163 bp molecule while the A. valvata mitogenome possesses two distinct circular molecules, 781,709 and 301,558 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
4
2
0
Order By: Relevance
“…Meanwhile, evolutionary analysis based on 12 core genes also supports this conclusion in which the relationship of A. macrosperma was closer to A. valvata, A. chinensis, and A. deliciosa, while it was distantly related to A. arguta of Kiwifruit species (Figure 5). Earlier research findings was consistent with the primary conclusions mentioned above, as indicated by evolutionary studies based on the Actinidia mitogenome, showing a closer genetic distance among A. chinensis, A. deliciosa, and A. valvata, while being more distantly related to A. valvata [59].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Meanwhile, evolutionary analysis based on 12 core genes also supports this conclusion in which the relationship of A. macrosperma was closer to A. valvata, A. chinensis, and A. deliciosa, while it was distantly related to A. arguta of Kiwifruit species (Figure 5). Earlier research findings was consistent with the primary conclusions mentioned above, as indicated by evolutionary studies based on the Actinidia mitogenome, showing a closer genetic distance among A. chinensis, A. deliciosa, and A. valvata, while being more distantly related to A. valvata [59].…”
Section: Discussionsupporting
confidence: 91%
“…Through examination of the correlation between SNPs and gene mutations, comprehensive insights into genome-wide gene mutations can be obtained, enabling the inference of the evolutionary trajectory of the entire species and its underlying causes: positive selection for active adaptation to the environment, negative selection resulting from environmental pressures, or neutral selection to maintain a balance between the two. Consistent with previous research [52,59,70], the majority of mitochondrial genes underwent neutral evolution under the influence of negative selection, displaying a high degree of conservation. However, positive selection may impact genes such as atp4 and ccmB, as indicated by their dN/dS ratio surpassing 1.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations